(untitled) (Materiali di Estetica. Terza serie, 2017)
Through an analysis of some crucial passages from Walter Benjamin’s On Language as Such and the Language of Man and The Origin of German Tragic Drama, the paper discusses the role and significance of the notion of "allegory" in philosophy and offers some insights into the idea of relationship between Benjamin’s notion of "allegory" and the “analogy” from the point of view of system theory, synthesis and exhibition of a radical negativity beyond any conceptual understanding.